The Economic Impact of Corporate Capital Expenditures: Focused Firms versus Diversified Firms - Chen, Sheng-Syan (Journal of Financial and Quantitative Analysis, 2006)
Abstract This paper examines the role of focus versus diversification in explaining the economic impact of corporate capital investments. I find that the stock market's responses to announcements of capital investments are more favorable for focused firms than for diversified firms. I also show that focused firms exhibit significantly better post-investment operating performance than diversified firms. The overall findings in this study suggest that the investment opportunities hypothesis dominates the internal capital markets hypothesis in terms of the net economic impact of capital investments on the investing firms.